2013
DOI: 10.7249/rr510
|View full text |Cite
|
Sign up to set email alerts
|

Multinational overview of cannabis production regimes

Abstract: is an independent, not-for-prof it policy research orga nisation t hat a ims to improve polic y a nd decisionma k ing for t he public interest t hough resea rch a nd a na lysis. R A ND's publications do not necessarily ref lect the opinions of its research clients and sponsors. R ® is a registered trademark © 2013 WODC, Ministerie van Veiligheid en Justitie. Auteursrechten voorbehouden. Niets uit dit rapport mag worden verveelvuldigd en/of openbaar gemaakt door middel van druk, fotokopie, microfilm, digitale v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…Nevertheless, they continue to operate in a vulnerable legal context (Pardal, 2016a). Despite the Belgian prohibition on cannabis supply, CSCs have based their actions on their interpretation of a policy guideline issued in 2005 by the Minister of Justice and the College of Public Prosecutors (Kilmer et al, 2013; Pardal, 2016a, 2018a). This Ministerial Guideline assigned the lowest priority to the prosecution of cases involving the possession of a maximum of 3 g of cannabis or one cannabis plant (in the absence of aggravating circumstances or disturbance to the public order).…”
Section: The Belgian Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they continue to operate in a vulnerable legal context (Pardal, 2016a). Despite the Belgian prohibition on cannabis supply, CSCs have based their actions on their interpretation of a policy guideline issued in 2005 by the Minister of Justice and the College of Public Prosecutors (Kilmer et al, 2013; Pardal, 2016a, 2018a). This Ministerial Guideline assigned the lowest priority to the prosecution of cases involving the possession of a maximum of 3 g of cannabis or one cannabis plant (in the absence of aggravating circumstances or disturbance to the public order).…”
Section: The Belgian Contextmentioning
confidence: 99%
“…Cannabis Social Clubs (CSCs) emerged as a result of grassroots initiatives of groups of adult cannabis users who sought to create a model of (collective) self-supply, by ensuring the cultivation and distribution of cannabis among themselves, on a closed and nonprofit basis (Bewley-Taylor, Blickman, & Jelsma, 2014; Blickman, 2014; Kilmer, Kruithof, Pardal, Caulkins, & Rubin, 2013; Pardal, 2016b). The first such initiatives emerged in Spain during the 1990s (Arana & Montañés, 2011; Barriuso, 2011, 2012; Marín, 2008, 2009; Montañés, 2017; Parés & Bouso, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Between 2010 and 2011, different groups of lawmakers sponsored a number of proposals to regulate individual cultivation of cannabis plants and the amount allowed for personal use. These bills were ultimately unsuccessful (Kilmer et al, 2013). At the same time, several civil society organizations mobilized in favor of more comprehensive legalization law (Garat, 2015).…”
Section: Marijuana Legalization In Uruguay and The United Statesmentioning
confidence: 99%
“…Despite the role that pro-legalization activists played in pushing for policy change, it is doubtful that the regulation of cannabis would have been approved if it had depended on the type of popular referendum used to advance legalization in the United States. In fact, surveys conducted throughout 2013 showed that more than 61% of Uruguayans did not support the bill (Garat, 2015; Kilmer et al, 2013).…”
Section: Marijuana Legalization In Uruguay and The United Statesmentioning
confidence: 99%
See 1 more Smart Citation